The "uncovered inflation rate parity" condition in a monetary union - Nicola Acocella; Paolo Pasimeni (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
The uncovered interest rate parity condition lies at the heart of the "impossible trinity", stating that the three objectives of fixed exchange rates, free capital flows, and independent monetary policy cannot be pursued simultaneously. We argue that although monetary unification does indeed eliminate the tension between exchange rates and nominal interest rates, it does not solve the problem of the intrinsic instability of the system. By eliminating the intra-area exchange rates (with a single currency) and interest rate differentials (with a single common policy rate set by the common central bank), the problem of instability is simply transferred to inflation rate differentials, what we call the (impossibility of the) "uncovered inflation rate parity condition" in a monetary union. The analysis of the actual divergences and imbalances in the EMU, then, suggests that failure to respect the "uncovered inflation rate parity condition" in a monetary union may lead to increasing economic and political tensions. Thus we conclude with the application of the Rodrik's political trilemma to the EMU, which epitomises the existential challenges that the EU faces nowadays.
Keywords: E42; F33; F41; F42; 330; Monetary Union; interest rate; exchange rate; inflation differentials; political trilemma